TREN PENELITIAN ARTIFICIAL INTELLIGENCE DALAM BIDANG SOSIAL DAN HUMANIORA: KAJIAN SCIENTOMETRIKA PADA DATABASE SCOPUS TAHUN 2015–2025 - Sanjaya, Riyan (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the scientific publication trends on Artificial Intelligence (AI) in the fields of social sciences and humanities through a scientometric approach. The main issue addressed is the lack of systematic mapping of AI research development in social and humanistic contexts based on bibliometric data. The study employs a quantitative descriptive method with scientometric analysis using publication data from the Scopus database from 2015 to 2025. The analysis focuses on identifying publication trends, the most productive authors and institutions, scientific collaboration, and emerging core themes. The findings reveal a significant increase in publication volume, the dominance of institutions from developed countries, and the emergence of research clusters focusing on ethics, education, economics, and psychology. The study concludes that AI has become an integral part of social and humanities studies with increasingly interdisciplinary approaches. This research is expected to serve as an important reference for academics and policymakers in developing evidence-based research strategies and policies.